Perlindungan Tenaga Kerja Indonesia (TKI) di Luar Negeri (Studi Kasus Mantan TKI di Dusun Curah Lele Desa Wonoasri Kecamatan Tempurejo Kabupaten Jember) - Mohammad Hafidz (Fakultas Hukum Universitas Islam Jember, 2018)
Wonoasri Village is one of the villages from Tempurejo Subdistrict which has 5 hamlets, one of which is the Lele Bulk Hamlet. Data from Wonoasri Village is estimated that there are more than 100 people in each hamlet who have worked abroad, but the data that has not been fully reported to the village office to work abroad. Most of the residents of Wonoasri Village choose to work as migrant workers who work abroad. The role of the Wonoasri Village Government and the Regional Government of Jember is needed to carry out the sending of Indonesian migrant workers abroad. In the sense that the government only provides employment information, but when it is implemented the village government and local government tend to be quiet and allow prospective workers to manage themselves with the PJTKI.